This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: c=-15-4b Then, by plugging in b for c, we get an equation that we can solve for b= -15-4b 0= -15-5b 15= -5b-3=b And since b=c, the value for both variables that will give us a horizontal tangent is b= -3 c= -3 C) Now we must find if there is a quadratic f(x)=e x p(x) that has only one horizontal tangent, and if it does, what restrictions would this put on b and c Once again we need to take the answer from the first equation x 2 +(2+b)x+b+c=0. Then we use the quadratic formula. (-(2+b) +/- sqrt((2+b) 2-4(b+c)))/2 Then we can look at just the numerator and set both the plus and the minus equal to each other-(2+b) + sqrt((2+b) 2-4(b+c))= -(2+b) - sqrt((2+b) 2-4(b+c)) Looking at this, it becomes evident that there can only be a horizontal tangent if (2+b) 2-4(b+c) = 0...
View Full Document
This note was uploaded on 04/13/2008 for the course MATH 021 taught by Professor Muralee during the Spring '08 term at Lehigh University .
- Spring '08